2019
DOI: 10.2172/1617811
|View full text |Cite
|
Sign up to set email alerts
|

Testing of an Iodine and Tritium Capture System for an NO₂-Based Tritium Pretreatment Process

Abstract: The reprocessing of used nuclear fuel would release volatile radionuclides into the off-gas streams of a processing plant, including 3 H, 14 C, 85 Kr, and 129 I. One potential simplification to the management of the off-gas streams could be achieved through an efficient tritium pretreatment (TPT) step in which the UO2 fuel is oxidized by either air or NO2 before dissolution. The oxidation of the UO2 fuel matrix will result in the release of tritium from the fuel. Upfront release of tritium from the fuel in a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Conventional voloxidation has been shown to release >99.9% of the tritium in the fuel but may not release tritium trapped as zirconium hydride deep within the cladding (Uchiyama et al 1992). Quantitative tritium volatilization and its capture on silica gel was demonstrated with tritiated water in the advanced voloxidation process (Jubin et al 2019). October 2023…”
Section: Voloxidationmentioning
confidence: 99%
“…Conventional voloxidation has been shown to release >99.9% of the tritium in the fuel but may not release tritium trapped as zirconium hydride deep within the cladding (Uchiyama et al 1992). Quantitative tritium volatilization and its capture on silica gel was demonstrated with tritiated water in the advanced voloxidation process (Jubin et al 2019). October 2023…”
Section: Voloxidationmentioning
confidence: 99%
“…This compound is stable under most industrial conditions, therefore AgZ likely not suitable for regeneration. Jubin et al (2019) attempted regeneration of iodine-loaded AgZ and AgNO 3 -impregnated alumina at 200°C and found that less than 1% of the adsorbed iodine was released over 3 h.…”
Section: Iodine Abatement Experimentsmentioning
confidence: 99%
“…The capture of I species and 3 H was investigated at Oak Ridge National Laboratory in earlier studies. (Greaney et al 2020, Jubin et al 2019. Silver mordenite was identified as an optimal trap for I species.…”
Section: Off-gas Capture Technologiesmentioning
confidence: 99%